1998
DOI: 10.1021/ma981017t
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Aspects of the Thermoreversible Gelation of Syndiotactic Poly(methyl methacrylate) in Toluene

Abstract: The thermoreversible gelation of syndiotactic poly(methyl methacrylate) in toluene has been investigated in detail. The two-step mechanism, proposed in an earlier publication, has been confirmed and illustrated in detail through the combination of FTIR investigations and rheological and NMR observations. The basic steps of this gelation mechanism are the equilibrium coil-to-single helix transition (first step) and the helix association into dimers (second steps) and larger multichain association units. The coi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
48
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 11 publications
3
48
0
Order By: Relevance
“…The straight line nature of the plots support that coil‐to‐rod transition is the first step of the gelation processes in both the systems. This mechanism is similar to the gelation of poly (vinylidine fluoride) (PVF 2 ) in glyceryl tributyrate or in diesters26, 27 and syn‐PMMA in toluene 37. The former polymer transforms from coil to TGTG conformer while the later one transforms from coil‐to‐helix structure prior to aggregation (gelation).…”
Section: Resultsmentioning
confidence: 66%
“…The straight line nature of the plots support that coil‐to‐rod transition is the first step of the gelation processes in both the systems. This mechanism is similar to the gelation of poly (vinylidine fluoride) (PVF 2 ) in glyceryl tributyrate or in diesters26, 27 and syn‐PMMA in toluene 37. The former polymer transforms from coil to TGTG conformer while the later one transforms from coil‐to‐helix structure prior to aggregation (gelation).…”
Section: Resultsmentioning
confidence: 66%
“…[10] A st-PMMA gel started melting at around 40 8C, while the st-PMMA/C 60 gel maintained its gel structure over 60 8C resulting from encapsulation of the C 60 molecules within the helical cavity of st-PMMA, thereby acting to reinforce the st-PMMA physical gel ( Figure S2 and Table S1 in the Supporting Information). [10] A st-PMMA gel started melting at around 40 8C, while the st-PMMA/C 60 gel maintained its gel structure over 60 8C resulting from encapsulation of the C 60 molecules within the helical cavity of st-PMMA, thereby acting to reinforce the st-PMMA physical gel ( Figure S2 and Table S1 in the Supporting Information).…”
mentioning
confidence: 99%
“…We then investigated the thermal stabilities of the st-PMMA and st-PMMA/C 60 gels by measuring their melting behavior using 1 H NMR spectroscopy. [10] A st-PMMA gel started melting at around 40 8C, while the st-PMMA/C 60 gel maintained its gel structure over 60 8C resulting from encapsulation of the C 60 molecules within the helical cavity of st-PMMA, thereby acting to reinforce the st-PMMA physical gel ( Figure S2 and Table S1 in the Supporting Information). Differential scanning calorimetry (DSC) and X-ray diffraction (XRD) profiles of the st-PMMA/C 60 films with different C 60 contents (11.7 and 23.5 wt %) revealed a crystalline structure of the st-PMMA/ C 60 complex ( Figure 2) that is essentially different from that of the st-PMMA film.…”
mentioning
confidence: 99%
“…1,4,5,119,120 Recently, a similar two-step mechanism of gelation through coil/helix transition was confirmed for synthetic polymers with stereo-regularity. 121,122 It was found that, in solutions of syndiotactic poly(methyl methacrylate) in toluene, a fast intramolecular conformational change is followed by an intermolecular association leading eventually to gelation.…”
Section: Gelation Triggared By Polymer Conformational Transitionmentioning
confidence: 99%